1976
DOI: 10.1111/j.1440-1827.1976.tb00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Sanfilippo B Syndrome — A Case Report —

Abstract: The presence of granulomas in the skin of T-cell lymphoma patients is a rare but well-known phenomenon. The authors present the case of a 44-year-old Caucasian male, with a previously treated peripheral T-cell lymphoma, with cutaneous infiltration and extensive dyschromia on his lower limbs. Skin biopsies revealed the presence of sarcoid granulomas associated with the recurrence of the lymphoma, confirmed by immunostaining and molecular analysis. Although a new scheme of chemotherapy was started , he died 18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
2
18
1
Order By: Relevance
“…Coronary artery narrowing and/or occlusion has been described in individuals with all types of MPS (Braunlin et al 1992; Brosius and Roberts 1981; Danks et al 1972; Factor et al 1978; Kettles et al 2002; Kurihara et al 1996; Renteria et al 1976; Shimamura et al 1976; Tan et al 1992), but is most common in MPS I and MPS II. Diffuse intimal proliferation from GAG deposition within large epicardial coronary arteries can occur early, especially in rapidly progressing MPS I (Brosius and Roberts 1981), causing high-grade narrowing (Fig.…”
Section: Cardiac Disease Associated With Mpsmentioning
confidence: 99%
“…Coronary artery narrowing and/or occlusion has been described in individuals with all types of MPS (Braunlin et al 1992; Brosius and Roberts 1981; Danks et al 1972; Factor et al 1978; Kettles et al 2002; Kurihara et al 1996; Renteria et al 1976; Shimamura et al 1976; Tan et al 1992), but is most common in MPS I and MPS II. Diffuse intimal proliferation from GAG deposition within large epicardial coronary arteries can occur early, especially in rapidly progressing MPS I (Brosius and Roberts 1981), causing high-grade narrowing (Fig.…”
Section: Cardiac Disease Associated With Mpsmentioning
confidence: 99%
“…(3) sulfatide standard; (4, 5) gray matter of mucopolysaccharidosis IH; (6) whole brain (control); (7) whole brain (patient); (8) TaySachs disease (whole brain). axon terminals in this case, is unclear.…”
Section: Biochemical Findingsmentioning
confidence: 99%
“…In the gray matter: non significant changes in the level of glycoprotein sugar from the insoluble membrane fraction whereas in the soluble "cytosol" fraction glucose, fucose and mannose were increased and N-acetylglycosamine was increased; 4) non significant changes in the total lipids and phospholipids; increase in cholesterol, cerebrosides and sulfatides in the gray matter and a decrease in all the lipid classes in the white matter due to the demyelination reported in this syndrome [33]; 5) increase in the GM2 and GD3 of the gray matter, in the GM3, GD3, GQI and GDIb of the white matter; presence in the Sanfilippo gray matter of GM4, a ganglioside not usually found in normal brain; 6) the lysosomal enzyme activities were increased with the exception of ~-galactosidase, which was decreased. In the gray matter: non significant changes in the level of glycoprotein sugar from the insoluble membrane fraction whereas in the soluble "cytosol" fraction glucose, fucose and mannose were increased and N-acetylglycosamine was increased; 4) non significant changes in the total lipids and phospholipids; increase in cholesterol, cerebrosides and sulfatides in the gray matter and a decrease in all the lipid classes in the white matter due to the demyelination reported in this syndrome [33]; 5) increase in the GM2 and GD3 of the gray matter, in the GM3, GD3, GQI and GDIb of the white matter; presence in the Sanfilippo gray matter of GM4, a ganglioside not usually found in normal brain; 6) the lysosomal enzyme activities were increased with the exception of ~-galactosidase, which was decreased.…”
Section: Sanfilippo: Neurochemistry Of Mucopolysaccharidosis 111 Amentioning
confidence: 85%
“…Biochemical studies showed the'existence of two types of the disease, A and B, according to the type of enzyme deficiency [22,23,24,27]. While neurochemical studies of this syndrome as well as of other types of mucopolysaccharidoses have been reported [8,9,10,11,33,38] no information is available on changes in glycoprotein levels in this syndrome. While neurochemical studies of this syndrome as well as of other types of mucopolysaccharidoses have been reported [8,9,10,11,33,38] no information is available on changes in glycoprotein levels in this syndrome.…”
Section: Introductionmentioning
confidence: 99%